2007
DOI: 10.1080/09603120701628669
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between outdoor air quality and respiratory symptoms in young children

Abstract: The aim of this study was to investigate the relationship between air pollution and respiratory symptoms in young children. A total of 263 children at high risk of developing asthma or atopy were recruited antenatally and all respiratory symptoms experienced by the children were recorded by their parents for five years. Daily pollutant concentrations and meteorological data (ambient temperature and humidity) were collected from network monitoring sites. Logistic regression models investigating relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Airways obstruction also appeared to be associated with higher subjective pollution levels, regardless of estimated levels from posted ambient ozone monitors. Similar to findings in other studies (30), these asthmatics had more frequent upper airway symptoms. Also, air pollution exposures were negatively associated with quality-of-life scores.…”
Section: Discussionsupporting
confidence: 90%
“…Airways obstruction also appeared to be associated with higher subjective pollution levels, regardless of estimated levels from posted ambient ozone monitors. Similar to findings in other studies (30), these asthmatics had more frequent upper airway symptoms. Also, air pollution exposures were negatively associated with quality-of-life scores.…”
Section: Discussionsupporting
confidence: 90%
“…For each increase of 1 mm 2 in carbon content they found a 12.9% decrease in FVC, a 17% decrease in FEV1 and a 34.7% decrease in FEF25-75%. Similar results have been reported for adults [4]. In a prospective study including 272 females, FRANCO et al [18] reported a 1.1% decrease (95% CI -2.5-0.3%) in FEV1, a 0.6% decrease (95% CI -1.9-0.6%) in FVC and a 3.0% decrease (95% CI -5.8--0.2%) in FEF25-75% for an interquartile range increase (22 mg?m The association we report here between EC and lower lung function was seen in both asthmatic and non-asthmatic children.…”
Section: Discussionsupporting
confidence: 80%
“…KEYWORDS: Air pollution, asthma, elemental carbon, epidemiology, lung function, schoolchildren V ehicular traffic is a major source of air pollutants and studies from different parts of the world have documented the relationship between exposure to air pollution and poorer respiratory health among children [1][2][3][4][5]. Children living in southern California who are exposed to traffic-related pollution have been reported to have lower lung function, with negative associations reported between the forced expiratory volume in 1 s (FEV1) and nitrogen dioxide, acid vapour, elemental carbon (EC) and particles with a mean aerodynamic diameter ,2.5 mm (PM2.5) [1].…”
Section: 1mentioning
confidence: 99%
“…Urban air monitoring is very important because high concentrations of contaminants in close proximity to humans can significantly amplify their exposure to metals, which are known to have detrimental effects on health (Dion et al 1993;Wong et al 2006). Exposure to air polluted with particulate matter containing diverse chemicals and heavy metals can trigger heart disease and many respiratory illnesses, especially in children and the elderly (Heinrich et al 2000;Rodriguez et al 2007). Metals such as Co, Cr, and Sb are reportedly found in the lungs as a result of the accumulation of air contaminants (Yaghi and Abdul-Wahab 2003).…”
Section: Introductionmentioning
confidence: 99%